PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN SERVICE DEPARTEMENT PADA PT ASTRA INTERNATIONAL, Tbk - DAIHATSU BRANCH OFFICE SEMARANG - Warastra Adhi Ramadya; Sudharto P Hadi; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
This study is about the Work Environment Influence and Compensation Section on Employee Satisfaction Services Department at PT Astra International, Tbk - Daihatsu Branch Office Semarang. This research was done due to the problems related to employee’s satisfaction predicted caused by the work environment and compensation . The objective of this study was to determine the influence of the work environment and compensation to employee satisfaction both partially and simultaneously. With this research, it can be taken a policy about work environment and compensation so that the company's goals can be achieved with optimal.The type of research is explanatory research. The population in this study were employees of the service department both general service and body repair as many as 40 people. Sampling technique used is the census so that the entire population is used as a sample. Thus technique sample used as many as 40 people. Data collection techniques are, interview and observation. The results of this study showsthatwork environment and compensation influenced on job satisfaction, partially or simultaneously. The result obtain by analyzing data with validity test, reliability test, t test, F test, the coefficient of determination and regression analysis. Calculations in this study using SPSS for Windows. Advice given is the company should maintain and improve the work environment that is both the physical environment, this is done by modulating the temperature in the work room so that it can support employees in work, set the level of noise, coloration that gives a fresh impression, relations between employees the fraternal relations between superiors and subordinates who can run well. Compensation is considered both direct and indirect compensation so that employees will be more satisfied in their work and performance will increase. Similar studies will be needed to add the variables apart from existing variables such as leadership, organizational culture, organizational commitment, work culture and work motivation that research on job satisfaction have become more perfect.